THE PREVALENCE OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS AT ADDINGTON HOSPITAL: A CROSS-SECTIONAL STUDY IN DURBAN, KWAZULU-NATAL. - Dube, Siphokazi Lulama; Shangase, Simangaliso Idiom (Student’s Journal of Health Research Africa, 2024)
Background Staphylococcus aureus (MRSA) is known to be a prominent public health issue that starts as a nosocomial infection that quickly escalates to catastrophic conditions such as pneumonia, necrotizing fasciitis, endocarditis, etc. The majority of Staphylococcus aureus infections among hospitalized patients are caused by methicillin-resistant Staph. aureus (HA-MRSA) which attributes 20–50% of Staph. aureus infections in South Africa. The aim and objectives of the study This study aims to evaluate the prevalence of Methicillin-Resistant Staphylococcus aureus (MRSA) at Addington Hospital and to monitor patterns of different classes of antibiotics tested on MRSA. Methodology This research study used a cross-sectional retrospective design with quantitative research analysis. Samples were tested for Microscopy, Culture, and Antibiotic Susceptibility in the microbiology laboratory from January 2021 to December 2021. The investigation focused on the sample population which tested positive for methicillin-resistant Staphylococcus aureus. It was recorded that a positive Staphylococcus aureus culture was used for quality control ensuring the accuracy of the results. Results Out of a total of 373 patients with Staphylococcus aureus isolates from different clinical specimens, 30(8.04%) were methicillin-resistant and 343 (91.96%) were methicillin-sensitive Staphylococcus aureus (MSSA). Antibiotic susceptibility tests showed that all patient samples were susceptible to vancomycin 373(100%). Conclusion The detection of 8.04% of MRSA in a hospital setting indicates that more work needs to be done to control MRSA prevalence.